Exosome-derived GTF2H2 from Huh7 cells can inhibit endothelial cell viability, migration, tube formation, and permeability. (December 2022) - Li, Zhenkun; Li, Yanmeng; Ouyang, Qin; Li, Xiaojin; Huang, Jian
Abstract: Hepatocellular carcinoma (HCC) is a leading cause of cancer-related morbidity and mortality worldwide. Given that HCC is an extraordinarily heterogeneous malignant disease, finding an effective therapeutic strategy for treating it has been difficult. Because of the importance of angiogenesis in tumorigenesis, targeting the more homogenous HCC endothelial cells may be a better therapeutic strategy. In a unpublished manuscript, we found that the expression levels of vascular endothelial growth factor receptor 2 (VEGFR2) and matrix metalloproteinase 2/9 (MMP2/9) were reduced in human HCC tissues that overexpressed DNA damage repair gene general transcription factor II subunit H2 (GTF2H2). This suggested that GTF2H2 may have an inhibitory effect on angiogenesis. Therefore, we hypothesized that GTF2H2 acts as an anti-angiogenesis gene. However, our results showed that GTF2H2 overexpression had no effect on endothelial cell viability, migration, or permeability. To our surprise, treating human umbilical vein endothelial cells (HUVECs) with the culture medium of Huh 7 cells overexpressing GTF2H2 could inhibit their viability, migration, and permeability. We then isolated the culture medium into exosomes and other components from the culture medium. Only GTF2H2-enriched exosomes could inhibit the viability, migration, tube formation, and permeability of HUVECs. Our results suggest that overexpressing GTF2H2 had no effect on HUVECs, while GTF2H2 enriched exosomes from Huh7 cells could inhibit HUVEC phenotypes such as proliferation and migration. Therefore, GTF2H2-enriched exosomes can possibly be utilized as a novel drug for treating HCC and also serve as a potential molecular target for inhibiting tumor angiogenesis. Graphical Abstract: ga1 Highlights: GTF2H2 overexpression had no effect on HUVECs. GTF2H2 overexpression Huh7 cells could inhibit viability, migration ability, tube formation and permeability of HUVECs. Only GTF2H2 enriched exosomes could inhibit viability, migration ability, tube formation and permeability of HUVECs.